CONSTRUCTION OF CHARACTER EDUCATION SYSTEM ACCORDING TO HAMKA - Hayatudin, Hayatudin; Munir, Munir; Hadi, Abdul (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Character education plays a crucial role in shaping a generation that excels not only academically but also morally. In this context, HAMKA’s educational philosophy offers significant insights for developing an Islamic-based character education system. Purpose: This study aims to identify, analyze, and examine HAMKA’s construction of character education by focusing on three core components: input, process, and output. Method: A qualitative library research approach was employed by analyzing HAMKA’s writings and related literature, incorporating perspectives from psychology, sociology, and education to achieve a comprehensive understanding. Result: The findings reveal that HAMKA's character education system comprises: (1) input, including a character-based curriculum, educators as role models, a supportive learning environment, and the involvement of parents and the community; (2) process, involving value integration into learning, habituation of good behavior, counseling, and character assessment; and (3) output, resulting in individuals with noble character, emotional and social intelligence, independence, responsibility, and adaptability in diverse societies. HAMKA emphasizes a holistic and integrated approach that demands collaboration among educational institutions, educators, families, and communities to foster character formation aligned with Islamic values. Conclusion: This study affirms that HAMKA’s character education model remains highly relevant and applicable in contemporary educational contexts, offering practical guidance for implementing morally grounded education within modern Islamic schools.